Optimasi Pemanfaatan Ulva lactuca Sebagai Seasoning: Studi Pada Produk Bakso Goreng, Kerupuk, Dan Keripik Ikan Lele - Sumandiarsa, I Ketut; Mahayani, Ni Kadek IDN; Hidayah, Nur; Sakti, Indra; Sirait, Jaulim (Universitas Negeri Gorontalo, 2025)
Ulva lactuca is a green macroalgae that can be found in all regions of Indonesia with high nutrition and applicable for food ingredient. The potential utilization in food that needs to be explored and researched is as seasoning or food flavoring. Seasoning can be added to various processed fish products and one of them is catfish which is a freshwater fish with abundant raw materials in Indonesia. This study aims to determine the quality of seasoning and the effect of its addition to processed catfish products, namely fried meatballs, crackers, and chips with three different percentages (5, 10, and 15%). The research method of completely randomized design and analysis of variance were used to determine the effect of seasoning treatment based on the proximate composition of each product and sensory testing. The results showed that the proximate value of the main parameter, namely protein, from the three products produced 10.2-11.8% in fried meatballs, 1.9-2.6% in cracker products, and 26.4-28.1%. Total Plate Count (TPL) showed varied results, namely 2.42 x 102 - 1.97 x 105 colonies/g (fried meatballs), 4.05 x 102 - 1.58 x 105 colonies/g (crackers), and 1.79 x 102 - 1.6 x 105 colonies/g (chips). The sensory value of all products was in the range of 6-8 or between liking and really liking. In addition, the analysis of variance (ANOVA) of the addition of seasonings had a significant effect (p 0.05) on the ash and protein parameters of all products. Furthermore, de Garmo analysis showed that the selected products in fried meatballs and chips were found in the addition of 15% seasoning, and in crackers were found in the addition of 10% seasoning.